Human Syngamosis as an Uncommon Cause of Chronic Cough - Pulcherio, Janaína Oliveira Bentivi; Machado da Silva, Eduardo Oliveira; Rezende, Daniela Pereira; Barbeira, Patrícia Bittencourt Barcia; Machado, Rosane Siciliano; Baptista de Oliveira, Marcos Aurélio (International Archives of Otorhinolaryngology, 2013)
Introduction Chronic cough may represent a diagnostic challenge. Chronic parasitism of upper airways is an unusual cause.Objective To describe a case of human syngamosis as an uncommon cause of dry cough.Case Report An endoscopic exam performed in a woman suffering of chronic cough revealed a Y-shaped worm in the larynx identified as Syngamus laryngeus.Discussion This nematode parasitizes the upper respiratory tract of many animals including humans. The diagnosis is performed by the examination of the worm expelled by cough or by endoscopy. Endoscopic exam is easy to perform and is essential in the diagnosis of causes of chronic cough, even uncommon entities. Removal is the only efficient treatment.
Keywords: cough; parasites; larynx